Application of Vyshnegradky's diagrams for transient analysis in electric discharge installations with stochastic load - Shcherba, M.A.; Suprunovska, N.I. (Електротехніка і електромеханіка, 2018)
Purpose. To analyze the transient processes in the discharge circuit of reservoir capacitor of electric discharge installations at a change in the circuit configuration during the discharge as well as to determine the appropriate circuit parameters for which the discharge process described by the third-order differential equation remains a damped oscillatory process. Methodology. We have applied the concepts of theoretical electrical engineering, the principles of theory of electrical circuits, theory of automatic control systems and mathematical simulation in the software package MathCAD 12. Results. We have obtained the analytical expressions and graphical dependencies that allow us to determine a relationship between the value of the element parameters of the discharge circuit of installations with an additional active-inductive chain and the character of the transient discharge process without solving a third-order differential equation. Originality. Using Vyshnegradsky's criteria and their graphical representations in the form of diagrams, we have proposed the procedure for determining the inductance value in additional chain shunting the capacitor of electric discharge installation in order to avoid the undesirable aperiodic discharge transient process in the stochastic load. Practical value. The use of this approach makes it possible to determine the ranges of the expedient change in the additional inductance at different load resistances for the realization of transient process required by the technology – the oscillatory discharge of the reservoir capacitor trough the load. Цель. Целью статьи является анализ переходных процессов в разрядной цепи накопительного конденсатора электроразрядных установок при изменении ее конфигурации во время разряда и определение целесообразных параметров цепи, при которых процесс разряда, описываемый дифференциальным уравнением третьего порядка, остается затухающим колебательным процессом. Методика. Для проведения исследований использовались научные положения теоретической электротехники, теория электрических цепей, теория систем автоматического регулирования и математическое моделирование в программном пакете MathCAD 12. Результаты. Получены аналитические выражения и графические зависимости, устанавливающие связь между значениями параметров элементов разрядной цепи установок с дополнительной активно-индуктивной цепочкой и характером переходного процесса разряда конденсатора без решения дифференциального уравнения третьего порядка. Научная новизна. Используя критерии Вышнеградского и их графические изображения в виде диаграмм, предложена методика определения величины индуктивности дополнительной цепочки, шунтирующей конденсатор электроразрядной установки, для исключения его нежелательного апериодического разряда на стохастическую нагрузку. Практическое значение. Использование данного подхода позволяет определить диапазоны целесообразного изменения дополнительной индуктивности при различных сопротивлениях нагрузки для реализации необходимого для технологии переходного процесса – колебательного разряда накопительного конденсатора на нагрузку